(untitled) (London Journal of Research In Humanities and Social Sciences, 2023)
Even though there are other forms of punishment such as fines, community service order, and probation service among others for convicted offenders, imprisonment is the most commonly applied world over, particularly for felonies. Sending convicts to prison is driven by the belief that incarceration is the best measure of ensuring protection of the society. Nevertheless, imprisonment is also common because it is awarded as an alternative to fines and other financial penalties for petty offenders who cannot afford the financial conditions due to poverty. However, in Kenya like in other jurisdictions, this form of punishment is characterized by weaknesses which have over the years made it a failure in its key mandates of reformation, rehabilitation, retribution, incapacitation and deterrence. This paper which is an outcome of a library research presents a brief origin of this form of punishment globally and in Kenya as well, discusses techniques employed in reformation, the demerits and weaknesses of imprisonment, and analyses its application in Kenya as a developing country. The paper concludes with recommendations on how effectiveness of imprisonment can be enhanced in the country.